Composite gel polymer electrolyte membrane, preparation method thereof and lithium ion battery
By using inorganic nanofiber porous films and lithium salts in composite solid electrolytes for ring-open polymerization reactions, the composite gel polymer electrolyte membrane is prepared, which solves the problem of easy agglomeration of inorganic fillers and improves lithium ion transport capability and mechanical properties.
Patent Information
- Application Number
- CN202411940842.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-01
AI Technical Summary
Inorganic fillers in existing composite solid electrolytes are prone to agglomeration, hindering lithium ion transmission and reducing mechanical properties.
The composite gel polymer electrolyte membrane is prepared by mixing the inorganic nanofiber porous film with lithium salt, ring opening initiator and cyclic polymer monomer solution.
The agglomeration of inorganic nanofibers is avoided, and the lithium ion transport capability and tensile strength of the composite gel polymer electrolyte membrane are enhanced, showing excellent ionic conductivity and mechanical properties.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a composite gel polymer electrolyte membrane and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Solid electrolytes can be divided into inorganic solid electrolytes, polymer solid electrolytes and composite solid electrolytes. Inorganic solid electrolytes have high ionic conductivity at room temperature, which is close to that of liquid electrolytes, but they are brittle and cannot be processed on a large scale; polymer solid electrolytes have strong processability, but their ionic conductivity is low at room temperature. Composite solid electrolytes can combine the advantages of both and make up for their disadvantages.
[0003] The transmission paths of lithium ions in composite solid electrolytes mainly include polymer matrix, inorganic matter and inorganic-polymer interface. When the filler concentration is too high, the filler will agglomerate, which will hinder the ion transmission of lithium ions in the polymer matrix and inorganic-polymer interface. In addition, too high filler concentration will reduce the mechanical properties of the overall solid electrolyte.
[0004] Therefore, there is an urgent need to provide a manufacturing process to solve the problem of easy agglomeration of inorganic fillers. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a composite gel polymer electrolyte membrane and a preparation method thereof and a lithium ion battery. The preparation method provided by the present invention simplifies the manufacturing process, not only avoids the agglomeration problem of inorganic nanofibers, but also utilizes the inorganic nanofiber porous film to enhance the lithium ion transmission capacity and tensile strength of the composite gel polymer electrolyte membrane, showing excellent ionic conductivity and mechanical properties.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a composite gel polymer electrolyte membrane, the preparation method comprising the following steps:
[0008] Provide an inorganic nanofiber porous film;
[0009] The lithium salt, the ring-opening initiator and the cyclic polymer monomer solution are mixed to obtain a mixed solution, and then the mixed solution and the inorganic nanofiber porous film are mixed to carry out a ring-opening polymerization reaction to obtain the composite gel polymer electrolyte membrane.
[0010] The preparation method provided by the present invention simplifies the manufacturing process, not only avoiding the agglomeration problem of inorganic nanofibers, but also utilizing the inorganic nanofiber porous film to enhance the lithium ion transmission capacity and tensile strength of the composite gel polymer electrolyte membrane, showing excellent ionic conductivity and mechanical properties.
[0011] Preferably, the inorganic nanofiber porous film has a thickness of 100-200 μm, for example, 100 μm, 120 μm, 130 μm, 140 μm, 150 μm, 160 μm, 180 μm or 200 μm.
[0012] In the present invention, the inorganic nanofiber porous film with a suitable thickness is helpful to improve its mechanical properties, and at the same time plays a role in reducing the crystallinity of the in-situ gel polymer electrolyte and improving the ability to transport lithium ions.
[0013] Preferably, in the inorganic nanofiber porous film, the fiber diameter is 100-400 nm, for example, 100 nm, 200 nm, 300 nm or 400 nm.
[0014] In the inorganic nanofiber porous film provided by the present invention, nanowires are arranged in a disordered manner, the thickness of the fibers is uniform, and the diameter of a single fiber is between 100nm and 400nm. The uniform nanofibers are beneficial to improving the flexibility and mechanical properties of the porous film.
[0015] Preferably, the inorganic nanofiber porous film has a porosity of 60-90%, for example, 60%, 65%, 70%, 75%, 80%, 85% or 90%.
[0016] In the present invention, the inorganic nanofiber porous film with appropriate porosity helps to ensure the liquid absorption and mechanical strength, and plays a role in enhancing the ionic conductivity of the gel electrolyte.
[0017] Preferably, the average pore size of the inorganic nanofiber porous film is 0.5-1 μm, for example, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm or 1 μm.
[0018] Preferably, the liquid absorption rate of the inorganic nanofiber porous film is 100-300%, for example, it can be 100%, 200% or 300%.
[0019] Preferably, the inorganic nanofiber porous film is selected from any one of a silica nanofiber porous film, an alumina nanofiber porous film or a boron nitride nanofiber porous film, preferably a silica nanofiber porous film.
[0020] Preferably, the method for preparing the inorganic nanofiber porous film comprises the following steps:
[0021] The solution containing the inorganic material and the polymer template solution are mixed to obtain a precursor solution.
[0022] The precursor solution is subjected to electrostatic spinning to obtain a composite film, and then the composite film is calcined to obtain the inorganic nanofiber porous film.
[0023] The present invention adopts electrostatic spinning technology to prepare a cross-linked polymer skeleton - inorganic nanofiber porous film, which is simple to operate and can realize continuous production; the diameter and morphology of the prepared nanofibers are controllable, and the nanofiber film has high porosity, high specific surface area and good mechanical properties, which solves the problem of easy agglomeration after adding inorganic fillers in traditional composite gel electrolytes, and finally plays a role in enhancing the ion transport of gel electrolytes.
[0024] Preferably, the polymer template solution includes any one of a polyvinyl alcohol solution, a polyethylene glycol solution or a polyacrylamide solution, or a combination of at least two of them.
[0025] Preferably, the concentration of the polymer template liquid is 8-12 wt%, for example, 8 wt%, 9 wt%, 10 wt%, 11 wt% or 12 wt%.
[0026] In the present invention, if the concentration of the polymer template liquid is too low, the solution viscosity is low, the polymer chains are insufficiently entangled, and the fibers cannot be fully stretched; if the concentration of the polymer template liquid is too high, the solution viscosity is high, the needle is easily clogged during electrospinning, and the non-spinnability increases.
[0027] Preferably, in the precursor solution, the mass content of the inorganic material is 20-30%, for example, 20%, 22%, 25%, 27% or 30%.
[0028] In the present invention, a suitable content of inorganic materials helps the inorganic nanofiber porous film to obtain excellent flexibility and mechanical properties.
[0029] Preferably, the calcination temperature is 600-1000°C, for example, 600°C, 700°C, 800°C, 900°C or 1000°C, and the calcination time is 1-6h, for example, 1h, 2h, 3h, 4h, 5h or 6h.
[0030] Preferably, the lithium salt includes any one of lithium borate, lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalatoborate or lithium dioxalatoborate, or a combination of at least two thereof.
[0031] Preferably, the ring-opening initiator includes any one of LiDFOB (lithium difluorooxalatoborate), LiC2BF2O4, LiBF4, LiBOB, LiPO2F2 or LiFSI (lithium bis(fluorosulfonyl)imide) or a combination of at least two thereof, preferably LiDFOB.
[0032] Preferably, the molar ratio of the lithium salt to the ring-opening initiator is (6-9):(1-4), wherein the selection range of the lithium salt "6-9" can be, for example, 6, 7, 8 or 9, and the selection range of the ring-opening initiator "1-4" can be, for example, 1, 2, 3 or 4.
[0033] In the present invention, lithium salt and ring-opening initiator in a suitable molar ratio are added to the cyclic polymer monomer solution, which can reduce the lattice energy of lithium salt, improve electrolyte conductivity, and widen the electrolyte electrochemical window. After the addition of some ring-opening initiators, in addition to the role of initiator, they can also play the role of electrolyte additives. For example, LiDFOB can form a protective layer on the surface of aluminum foil to inhibit the corrosion of bistrifluoromethanesulfonyl imide lithium salt on the current collector under high pressure.
[0034] Preferably, in the cyclic polymer monomer solution, the cyclic polymer monomer includes any one or a combination of at least two of 1,3-dioxolane (DOL), vinylene carbonate (VC), tetrahydrofuran (THF), polyethylene glycol dimethyl ether (PEGDE), fluorinated vinyl carbonate (FEC) or trioxymethylene (TOM).
[0035] In a preferred technical solution of the present invention, the ring-opening initiator is selected as LiDFOB (lithium difluorooxalate borate), and the cyclic polymer monomer is 1,3-dioxolane, and the following ring-opening polymerization process can be carried out:
[0036]
[0037] From the above, it can be seen that BF3 in lithium difluorooxalatoborate can react with trace water in DOL to generate H + (BF3OH) - , H + (BF3OH) - DOL can be induced to undergo in situ ring-opening polymerization to obtain poly(1,3-dioxolane) (PDOL).
[0038] Preferably, the cyclic polymer monomer solution also includes a plasticizer.
[0039] Preferably, the plasticizer comprises succinonitrile.
[0040] Preferably, the mass content of the plasticizer in the cyclic polymer monomer solution is 10-40%, for example, 10%, 20%, 30% or 40%.
[0041] Preferably, the temperature of the ring-opening polymerization reaction is 40-80°C, for example, 40°C, 50°C, 60°C, 70°C or 80°C.
[0042] Preferably, the isothermal time of the ring-opening polymerization reaction is 6-24 h, for example, 6 h, 12 h, 18 h or 24 h.
[0043] Preferably, the preparation method comprises the following steps:
[0044] (1) A silicon source solution (exemplarily, for example, a tetraethyl orthosilicate solution) having a concentration of 10-30 wt% (for example, 10 wt%, 15 wt%, 20 wt%, 25 wt% or 30 wt%) is prepared, and then the silicon source solution is mixed with a polymer template solution having a concentration of 8-12 wt%, and an acid solution is added for blending to obtain a precursor solution; the mass content of the silicon source in the precursor solution is 20-30%; and the acid solution comprises any one of hydrochloric acid, sulfuric acid or carbonic acid, or a combination of at least two of them.
[0045] The precursor solution is subjected to electrospinning, and then the obtained composite film is calcined to obtain an inorganic nanofiber porous film; wherein the specific parameters of the electrospinning include: a voltage of 10-15kV (for example, 10kV, 11kV, 12kV, 13kV, 14kV or 15kV, etc.), a receiving distance of 8-15cm (for example, 8cm, 10cm, 12cm or 15cm, etc.), a flow rate of 0.05-1mL / h (for example, 0.05mL / h, 0.1mL / h, 0.5mL / h or 1mL / h, etc.); the calcination temperature is 600-1000°C, and the time is 1-6h.
[0046] (2) Under stirring conditions, lithium salt and ring-opening initiator are dissolved in a cyclic polymer monomer solution containing 10-40% plasticizer in a molar ratio of (6-9):(1-4) to obtain a mixed solution, and then the inorganic nanofiber porous film is immersed in the mixed solution to carry out a ring-opening polymerization reaction at 40-80° C. for 6-24 hours to obtain the composite gel polymer electrolyte membrane.
[0047] In a second aspect, the present invention provides a composite gel polymer electrolyte membrane, which is prepared by the preparation method described in the first aspect.
[0048] Preferably, the ionic conductivity of the composite gel polymer electrolyte membrane is 0.1-1 mS / cm, for example, 0.1 mS / cm, 0.3 mS / cm, 0.5 mS / cm, 0.7 mS / cm or 0.9 mS / cm.
[0049] Preferably, the tensile strength of the gel polymer electrolyte membrane is 2-10 MPa, for example, 2 MPa, 4 MPa, 6 MPa, 8 MPa or 10 MPa.
[0050] Preferably, the porosity of the composite gel polymer electrolyte membrane is 10-30%, for example, 10%, 20% or 30%.
[0051] In a third aspect, the present invention provides a lithium ion battery, wherein the lithium ion battery comprises the composite gel polymer electrolyte membrane as described in the second aspect.
[0052] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0053] Compared with the prior art, the present invention has the following beneficial effects:
[0054] The preparation method provided by the present invention simplifies the manufacturing process, not only avoiding the agglomeration problem of inorganic nanofibers, but also utilizing the inorganic nanofiber porous film to enhance the lithium ion transmission capacity and tensile strength of the composite gel polymer electrolyte membrane, showing excellent ionic conductivity and mechanical properties. DETAILED DESCRIPTION
[0055] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0056] Example 1
[0057] This embodiment provides a method for preparing a composite gel polymer electrolyte membrane, the preparation method comprising the following steps:
[0058] (1) TEOS and deionized water are mixed to prepare a 15 wt % TEOS solution, and then the TEOS solution is mixed with a 10 wt % polymer template solution (i.e., polyvinyl alcohol solution), and an acid solution (i.e., hydrochloric acid) is added to blend the mixture to obtain a precursor solution; the mass content of TEOS in the precursor solution is 25%.
[0059] The precursor solution was subjected to electrospinning, and the obtained composite film was then calcined at 800° C. for 3 h to obtain a porous silica nanofiber film; wherein the specific parameters of the electrospinning included: a voltage of 12 kV, a receiving distance of 12 cm, and a flow rate of 0.5 mL / h.
[0060] The thickness of the silica nanofiber porous film is 140 μm, the fiber diameter is 250 nm, the porosity is 75%, the average pore size is 750 nm, and the liquid absorption rate is 245%.
[0061] (2) Under stirring conditions, lithium bis(trifluoromethylsulfonyl)imide and lithium difluorooxalatoborate are dissolved in a DOL solution containing 30% succinonitrile in a molar ratio of 8:2 to obtain a mixed solution, and then the silica nanofiber porous film is immersed in the mixed solution and subjected to a ring-opening polymerization reaction at 60° C. for 12 hours to obtain the composite gel polymer electrolyte membrane.
[0062] Example 2
[0063] This embodiment provides a method for preparing a composite gel polymer electrolyte membrane, the preparation method comprising the following steps:
[0064] (1) TEOS and deionized water are mixed to prepare a 10 wt% TEOS solution, and then the TEOS solution is mixed with an 8 wt% polymer template solution (i.e., a polyvinyl alcohol solution), and an acid solution (i.e., hydrochloric acid) is added to blend the mixture to obtain a precursor solution; the mass content of TEOS in the precursor solution is 20%.
[0065] The precursor solution was subjected to electrospinning, and the obtained composite film was then calcined at 600° C. for 6 h to obtain a porous silica nanofiber film; wherein the specific parameters of the electrospinning included: a voltage of 10 kV, a receiving distance of 15 cm, and a flow rate of 0.05 mL / h.
[0066] The thickness of the silica nanofiber porous film is 120 μm, the fiber diameter is 100 nm, the porosity is 90%, the average pore size is 0.5 μm, and the liquid absorption rate is 286%.
[0067] (2) Under stirring conditions, lithium bis(trifluoromethylsulfonyl)imide and lithium difluorooxalatoborate are dissolved in a DOL solution containing 10% succinonitrile in a molar ratio of 9:1 to obtain a mixed solution, and then the silica nanofiber porous film is immersed in the mixed solution and subjected to a ring-opening polymerization reaction at 40° C. for 24 hours to obtain the composite gel polymer electrolyte membrane.
[0068] Example 3
[0069] This embodiment provides a method for preparing a composite gel polymer electrolyte membrane, the preparation method comprising the following steps:
[0070] (1) TEOS and deionized water are mixed to prepare a 30 wt % TEOS solution, and then the TEOS solution is mixed with a 12 wt % polymer template solution (i.e., polyvinyl alcohol solution), and an acid solution (i.e., hydrochloric acid) is added to blend the mixture to obtain a precursor solution; the mass content of TEOS in the precursor solution is 30%.
[0071] The precursor solution is subjected to electrospinning, and then the obtained composite film is calcined at 1000° C. for 1 hour to obtain a porous silica nanofiber film; wherein the specific parameters of the electrospinning include: a voltage of 15 kV, a receiving distance of 8 cm, and a flow rate of 1 mL / h.
[0072] The thickness of the silica nanofiber porous film is 160 μm, the fiber diameter is 400 nm, the porosity is 60%, the average pore size is 1 μm, and the liquid absorption rate is 200%.
[0073] (2) Under stirring conditions, lithium bis(trifluoromethylsulfonyl)imide and lithium difluorooxalatoborate are dissolved in a DOL solution containing 40% succinonitrile in a molar ratio of 6:4 to obtain a mixed solution, and then the silica nanofiber porous film is immersed in the mixed solution and subjected to a ring-opening polymerization reaction at 80° C. for 6 hours to obtain the composite gel polymer electrolyte membrane.
[0074] Example 4
[0075] The difference between this embodiment and embodiment 1 is that the thickness of the porous silicon dioxide nanofiber film is 100 μm by adjusting the electrospinning parameters.
[0076] The rest of the preparation methods and parameters were the same as those in Example 1.
[0077] Example 5
[0078] The difference between this embodiment and embodiment 1 is that the thickness of the porous silicon dioxide nanofiber film is 180 μm by adjusting the electrospinning parameters.
[0079] The rest of the preparation methods and parameters were the same as those in Example 1.
[0080] Example 6
[0081] The difference between this embodiment and embodiment 1 is that the porosity of the silica nanofiber porous film is 50% by adjusting the electrospinning parameters.
[0082] The rest of the preparation methods and parameters were the same as those in Example 1.
[0083] Example 7
[0084] The difference between this embodiment and embodiment 1 is that the porosity of the silica nanofiber porous film is 95% by adjusting the electrospinning parameters.
[0085] The rest of the preparation methods and parameters were the same as those in Example 1.
[0086] Example 8
[0087] The difference between this embodiment and embodiment 1 is that the concentration of the polymer template liquid is 5 wt %.
[0088] The rest of the preparation methods and parameters were the same as those in Example 1.
[0089] Example 9
[0090] The difference between this embodiment and embodiment 1 is that the concentration of the polymer template liquid is 15 wt %.
[0091] The rest of the preparation methods and parameters were the same as those in Example 1.
[0092] Example 10
[0093] The difference between this embodiment and embodiment 1 is that the mass content of ethyl orthosilicate in the precursor solution is 15%.
[0094] The rest of the preparation methods and parameters were the same as those in Example 1.
[0095] Embodiment 11
[0096] The difference between this embodiment and embodiment 1 is that the mass content of ethyl orthosilicate in the precursor solution is 35%.
[0097] The rest of the preparation methods and parameters were the same as those in Example 1.
[0098] Example 12
[0099] The difference between this embodiment and embodiment 1 is that the molar ratio of lithium bis(trifluoromethylsulfonyl)imide to lithium difluorooxalatoborate is 5:5. The remaining preparation methods and parameters are the same as those in embodiment 1.
[0100] Example 13
[0101] The difference between this embodiment and embodiment 1 is that the molar ratio of lithium bis(trifluoromethylsulfonyl)imide to lithium difluorooxalatoborate is 9.5:0.5.
[0102] The rest of the preparation methods and parameters were the same as those in Example 1.
[0103] Comparative Example 1
[0104] The difference between this comparative example and Example 1 is that step (1) is not performed, and the silica nanofiber porous film in step (2) is replaced by glass fiber.
[0105] The rest of the preparation methods and parameters were the same as those in Example 1.
[0106] Performance Testing
[0107] 1. The porosity and liquid absorption rate of the silica nanofiber porous film provided in the above embodiment were tested.
[0108] The porosity test method is as follows: cut the film to be tested, measure the size of the film and weigh it, then use a true density meter to measure the true density of the diaphragm, and calculate the porosity of the film according to the porosity formula: P = (1-V 真 / V 表 )×100%, where P is the porosity of the film (%), V 真 is the true volume of the film (cm 3 ), V 表 is the apparent volume of the film (cm 3 ); The test method for liquid absorption rate is as follows: cut a film sample with uniform thickness and flat surface, measure its volume V1, put the container containing electrolyte on the electronic balance and return the reading to zero, fix the ring with a thin wire so that it is completely immersed in the electrolyte and suspended, record the balance reading M1, then fix the film sample to the ring, immerse it in the electrolyte for 30 minutes, record the balance reading M2, and finally calculate the liquid absorption rate according to the formula L = (ρV1+M1-M2) / V1, where ρ is the electrolyte density.
[0109] 2. The composite gel polymer electrolyte membranes provided in the above embodiments and comparative examples were tested, including ion conductivity test and tensile strength test.
[0110] The test method of ionic conductivity is as follows: a composite electrolyte membrane that has not undergone a ring-opening polymerization reaction (i.e., a porous silica nanofiber film or glass fiber soaked in a mixed solution in each embodiment or comparative example) is placed between two stainless steel sheets to assemble a test system, and then the battery is heated for in-situ curing. After curing, it is connected to an electrochemical workstation, and the AC impedance spectrum at different frequencies is measured. The resistance value is obtained by equivalent circuit fitting and the like, and then the ionic conductivity is calculated according to the formula σ=L / SR, where σ is the ionic conductivity, L is the electrode spacing, S is the electrode area, R is the resistance value; the test method of tensile strength is: cut the composite gel polymer electrolyte membrane into the required size, install the sample on the fixture of the tensile testing machine to ensure firm clamping, and then apply tensile force to the sample at a constant speed, while recording the force-displacement data until the sample breaks, find the maximum tensile force at break from the force-displacement curve, and calculate the tensile strength according to the formula σ=F / (b×d), where σ is the tensile strength (MPa), F is the force value (N), b is the sample width (mm), and d is the sample thickness (mm).
[0111] The test results are shown in Table 1.
[0112] Table 1
[0113]
[0114]
[0115] analyze:
[0116] The preparation method provided by the present invention simplifies the manufacturing process, not only avoiding the agglomeration problem of inorganic nanofibers, but also utilizing the inorganic nanofiber porous film to enhance the lithium ion transmission capacity and tensile strength of the composite gel polymer electrolyte membrane, showing excellent ionic conductivity and mechanical properties.
[0117] It can be seen from Example 1 and Examples 4-5 that if the thickness of the porous silica nanofiber film is small, its tensile strength will be reduced; if the thickness of the porous silica nanofiber film is large, its ionic conductivity will be reduced.
[0118] It can be seen from Examples 1 and 6-7 that if the porosity of the silica nanofiber porous film is too small, the liquid absorption rate and ionic conductivity will decrease; if the porosity of the silica nanofiber porous film is too large, the liquid absorption rate, ionic conductivity and tensile strength will all decrease.
[0119] It can be seen from Example 1 and Example 8-9 that if the concentration of the polymer template liquid is too low, the viscosity of the spinning solution is low, which will cause insufficient entanglement of the polymer chain, resulting in increased jet instability, and the inability to fully stretch the fiber, making the diameter of the nanofibers uneven, and the film-forming property of the calcined nanofiber porous film is poor; if the concentration of the polymer template liquid is too high, the polymer solution is easy to condense at the injection needle due to the small proportion of the solvent in the solution, and it is easy to clog the needle, thereby increasing the non-spinnability, and the nanofiber morphology of the spinning film is uneven, with coarse and fine diameters. Therefore, if the concentration of the polymer template liquid is too high or too low, the porosity, liquid absorption rate and ionic conductivity of the porous film will be reduced. If the concentration of the template liquid is too low, it will also affect the tensile strength of the porous film.
[0120] It can be seen from Examples 1 and 10-11 that if the mass content of tetraethyl orthosilicate in the precursor solution is too small, then due to insufficient silicon source, the bending and twisting of single nanofibers will be more serious, the fiber thickness will be uneven, and a large number of beads will be produced, and the flexibility and mechanical properties of the SiO2 nanofiber porous film will be poor; if the mass content of tetraethyl orthosilicate in the precursor solution is too large, then as the proportion of inorganic phase increases, the uniformity of the precursor solution deteriorates, the surface tension of the solution increases, the splitting and stretching ability of the droplets decreases after leaving the nozzle, the fibers cannot be fully stretched, causing the SiO2 nanofiber porous film to become coarser and the uniformity to deteriorate.
[0121] It can be seen from Example 1 and Examples 12-13 that if the molar ratio of lithium bis(trifluoromethylsulfonylimide) to lithium difluorooxalate borate is too small, the content of the initiator is too large, which will lead to an increase in the lattice energy of the lithium salt, a decrease in the ionic conductivity of the electrolyte, and a reduction in the electrochemical window of the electrolyte; if the molar ratio of lithium bis(trifluoromethylsulfonylimide) to lithium difluorooxalate borate is too large, the content of the initiator is too small, which will lead to incomplete in-situ polymerization, a decrease in the polymer chain segments in the electrolyte, a decrease in the ionic conductivity, and a decrease in the tensile strength of the composite gel electrolyte.
[0122] It can be seen from Example 1 and Comparative Example 1 that if the silica nanofiber porous film is replaced by glass fiber, the glass fiber has a poor effect of enhancing the ion transport and mechanical properties of the composite gel electrolyte, resulting in reduced ion conductivity and tensile strength of the composite gel electrolyte.
[0123] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a composite gel polymer electrolyte membrane, characterized in that: The preparation method comprises the following steps: Provide an inorganic nanofiber porous film; The lithium salt, the ring-opening initiator and the cyclic polymer monomer solution are mixed to obtain a mixed solution, and then the mixed solution and the inorganic nanofiber porous film are mixed to carry out a ring-opening polymerization reaction to obtain the composite gel polymer electrolyte membrane.
2. The preparation method according to claim 1, characterized in that: The thickness of the inorganic nanofiber porous film is 100-200 μm; Preferably, in the inorganic nanofiber porous film, the fiber diameter is 100-400 nm; Preferably, the inorganic nanofiber porous film has a porosity of 60-90%; Preferably, the average pore size of the inorganic nanofiber porous film is 0.5-1 μm; Preferably, the liquid absorption rate of the inorganic nanofiber porous film is 100-300%; Preferably, the inorganic nanofiber porous film is selected from any one of a silica nanofiber porous film, an alumina nanofiber film or a boron nitride nanofiber film.
3. The preparation method according to claim 1 or 2, characterized in that: The method for preparing the inorganic nanofiber porous film comprises the following steps: mixing a solution containing an inorganic material and a polymer template solution to obtain a precursor solution; The precursor solution is subjected to electrostatic spinning to obtain a composite film, and then the composite film is calcined to obtain the inorganic nanofiber porous film.
4. The preparation method according to claim 3, characterized in that: The polymer template solution includes any one of a polyvinyl alcohol solution, a polyethylene glycol solution or a polyacrylamide solution or a combination of at least two thereof; Preferably, the concentration of the polymer template liquid is 8-12wt%; Preferably, the mass content of the inorganic material in the precursor solution is 20-30%; Preferably, the calcination temperature is 600-1000° C. and the calcination time is 1-6 hours.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The lithium salt includes any one of lithium borate, lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium tetrafluoroborate, lithium difluorooxalatoborate or lithium dioxalatoborate, or a combination of at least two thereof; Preferably, the ring-opening initiator comprises any one or a combination of at least two of LiDFOB, LiC2BF2O4, LiBF4, LiBOB, LiPO2F2 or LiFSI; Preferably, the molar ratio of the lithium salt to the ring-opening initiator is (6-9):(1-4); Preferably, in the cyclic polymer monomer solution, the cyclic polymer monomer includes any one or a combination of at least two of 1,3-dioxolane, vinylene carbonate, tetrahydrofuran, polyethylene glycol dimethyl ether, fluorinated vinyl carbonate or trioxymethylene; Preferably, the cyclic polymer monomer solution further comprises a plasticizer; Preferably, the plasticizer comprises succinonitrile; Preferably, the mass content of the plasticizer in the cyclic polymer monomer solution is 10-40%.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The temperature of the ring-opening polymerization reaction is 40-80°C; Preferably, the constant temperature time of the ring-opening polymerization reaction is 6-24h.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The preparation method comprises the following steps: (1) preparing a silicon source solution with a concentration of 10-30wt%, then mixing the silicon source solution with a polymer template solution with a concentration of 8-12wt%, and adding an acid solution for blending to obtain a precursor solution; the mass content of the silicon source in the precursor solution is 20-30wt%; the acid solution includes any one of hydrochloric acid, sulfuric acid or carbonic acid, or a combination of at least two of them; The precursor solution is subjected to electrostatic spinning, and then the obtained composite film is calcined to obtain an inorganic nanofiber porous film; wherein the specific parameters of the electrostatic spinning include: a voltage of 10-15 kV, a receiving distance of 8-15 cm, and a flow rate of 0.05-1 mL / h; the calcination temperature is 600-1000° C., and the time is 1-6 h; (2) Under stirring conditions, lithium salt and ring-opening initiator are dissolved in a cyclic polymer monomer solution containing 10-40% plasticizer in a molar ratio of (6-9):(1-4) to obtain a mixed solution, and then the inorganic nanofiber porous film is immersed in the mixed solution to carry out a ring-opening polymerization reaction at 40-80° C. for 6-24 hours to obtain the composite gel polymer electrolyte membrane.
8. A composite gel polymer electrolyte membrane, characterized in that: The composite gel polymer electrolyte membrane is prepared by the preparation method according to any one of claims 1 to 7.
9. The composite gel polymer electrolyte membrane according to claim 8, characterized in that: The ionic conductivity of the composite gel polymer electrolyte membrane is 0.1-1 mS / cm; Preferably, the tensile strength of the composite gel polymer electrolyte membrane is 2-10 MPa; Preferably, the porosity of the composite gel polymer electrolyte membrane is 10-30%.
10. A lithium ion battery, characterized in that: The lithium ions include the composite gel polymer electrolyte membrane as claimed in claim 8 or 9.
Citation Information
Cited By
Composite electrolyte precursor and preparation method and application thereof
CN120089798A